An evaluation of alexithymia subtypes using latent profile analysis. (May 2021) - Bagby, R. Michael; Sanches, Marcos; Carnovale, Michael; Taylor, Graeme J.
Highlights: Some researchers have proposed the existence of 'alexithymia" subtypes. Other investigators, however, argue that alexithymia is a single dimensional trait. Latent profile analysis (LPA) evaluates the presence of types. No evidence emerged for alexithymia subtypes using LPA. Abstract: Four subtypes of the alexithymia construct have been proposed based on different response patterns to the Cognitive and Affective dimensions of the Bermond-Vorst Alexithymia Questionnaire (BVAQ). Previous studies investigating whether alexithymia subtypes can be statistically estimated have not found complete support for these specific subtypes. These previous studies, however, contained several methodological limitations such as relatively small sample sizes, and considerations of only a limited number of proposed subtypes. In the current investigation, we examined whether the four proposed subtypes could be statistically detected in a large sample of undergraduate students ( N  = 612) who completed the BVAQ, using latent profile analysis (LPA). Based on observed responses to the five BVAQ subscales, consistent with previous studies, our results did not find support for the four proposed alexithymia subtypes. Rather, our results suggested LPA solutions that correspond to individuals with various degrees of alexithymia 'severity'. Although further studies are needed, especially with clinical samples, these results question the idea of four alexithymia subtypes and suggest that the implementation of these subtypes into various research studies may be a premature endeavour.